ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENAWARAN TENAGA KERJA DI INDONESIA - Elsa Andrisani; Mike Triani (Universitas Negeri Padang, 2019)
the phenomenon of labor in Indonesian is that the workforce in increasing but there are few opportunities for employment. This will cause unemployment and many unemployment will effect the economy. Study aims to determine the impact of population growth , wages, and education on labor supply in Indonesia. This research used panel data from 2013 to 2018 in 34 provinces in Indonesia and analysis used panel data regression with FEM method. The results of the study found that; 1) population growth hasn’t impact on the labor supply in Indonesia. (2) Wages hasn’t impact on labor supply in Indonesia. (3) education has an impact on the labor supply in Indonesia.